Unusual haplotypic structure of IL8, a susceptibility locus for a common respiratory virus. - Hull, J; Ackerman, H; Isles, K; Usen, S; Pinder, M; Thomson, A; Kwiatkowski, D (2001)
Interleukin-8 (IL8) is believed to play a role in the pathogenesis of bronchiolitis, a common viral disease of infancy, and a recent U.K. family study identified an association between this disease and the IL8-251A allele. In the present study we report data, from a different set of families, which replicate this finding; combined analysis of 194 nuclear families through use of the transmission/disequilibrium test gives P = .001. To explore the underlying genetic cause, we identified nine single-nucleotide polymorphisms (SNPs) in a 7.6-kb segment spanning the IL8 gene and its promoter region and used six of these SNPs to define the haplotypic structure of the IL8 locus. The IL8-251A allele resides on two haplotypes, only one of which is associated with disease, suggesting that this may not be the functional allele. Europeans show an unusual haplotype genealogy that is dominated by two common haplotypes differing at multiple sites, whereas Africans have much greater haplotypic diversity. These marked haplotype-frequency differences give an F(ST) of.25, and, in the European sample, both Tajima's D statistic (D = 2.58, P = .007) and the Hudson/Kreitman/Aguade test (chi(2) = 4.9, P = .03) reject neutral equilibrium, suggesting that selective pressure may have acted on this locus.